Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1039/c2cc33823h
|View full text |Cite
|
Sign up to set email alerts
|

Photo- and thermally induced coloration of a crystalline MOF accompanying electron transfer and long-lived charge separation in a stable host–guest system

Abstract: A new type of electron transfer (ET) system was built via the combination of a highly stable MOF host framework and methyl viologen guest molecule. The π-stacking arrangements adjust the distance between the D-A components, contributing to the formation of an ultra long-lived charge separated state in the photo/thermo dual stimuli-responsive complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(59 citation statements)
references
References 32 publications
(20 reference statements)
3
56
0
Order By: Relevance
“…The donor component in this PET process can be either the carboxylate oxygen of the bpdc or the bpdc chromophoric linker itself, which are located at distances of 3.9 and 2.59 Å, respectively, from the electron‐deficient bpNDI linker (Figure 3 b). 10b Although similar photochromic behaviour in NDI‐based MOFs has been ascribed to a so called “π–π* electron transfer”,8d, e we show here that the reduction of bpNDI acceptors to radical anions would indeed require a PET mechanism wherein the presence of an electron‐donor group/molecule is mandatory.…”
Section: Methodssupporting
confidence: 58%
“…The donor component in this PET process can be either the carboxylate oxygen of the bpdc or the bpdc chromophoric linker itself, which are located at distances of 3.9 and 2.59 Å, respectively, from the electron‐deficient bpNDI linker (Figure 3 b). 10b Although similar photochromic behaviour in NDI‐based MOFs has been ascribed to a so called “π–π* electron transfer”,8d, e we show here that the reduction of bpNDI acceptors to radical anions would indeed require a PET mechanism wherein the presence of an electron‐donor group/molecule is mandatory.…”
Section: Methodssupporting
confidence: 58%
“…Bridged by L 2 , at rinuclear Cd1-Co3-Cd1 secondary building unit (SBU)i s generated and further linked with adjacent trinuclear SBU and Cd2 nodes to afford ah ighly-connected 3D framework. Thec ationic ligands CL 1 are thermally unstable and decompose into methyl viologen (MV) fragments, [20] which serve as guest molecules to fill the cavities of MOF 9.B yc arefully…”
Section: Angewandte Chemiementioning
confidence: 99%
“…To this end, the reagent for MOFs 5 (Co/CL 1 /L 2 )a nd 6 (Cd/ CL 1 /L 6 )w ere added into the two compartmentalized chambers to conduct multi-stage hydrothermal reactions.Asshown in Figure 4A,various crystal combinations could be obtained by varying the mixing time points t n . Thec ationic ligands CL 1 are thermally unstable and decompose into methyl viologen (MV) fragments, [20] which serve as guest molecules to fill the cavities of MOF 9.B yc arefully tuning the mixing point t n from 0t o3hours, an ew type of compound with hexagonal crystals began to form in addition to MOF 9 and the yield gradually increased when t n was varied from 3t o6hours ( Figure 4A). Single-crystal X-ray analysis revealed that 9 is composed of a3 Dn etwork constructed by connection of Cd and Co centres with L 2 ligands ( Figure 4B).…”
mentioning
confidence: 99%
“…Bridged by L 2 , a trinuclear Cd1‐Co3‐Cd1 secondary building unit (SBU) is generated and further linked with adjacent trinuclear SBU and Cd2 nodes to afford a highly‐connected 3D framework. The cationic ligands CL 1 are thermally unstable and decompose into methyl viologen (MV) fragments, which serve as guest molecules to fill the cavities of MOF 9 . By carefully tuning the mixing point t n from 0 to 3 hours, a new type of compound with hexagonal crystals began to form in addition to MOF 9 and the yield gradually increased when t n was varied from 3 to 6 hours (Figure A).…”
Section: Figurementioning
confidence: 99%